Does Influencer Marketing affect Customer Satisfaction: Evidence from Social Media Shoppers in Lagos, Nigeria - Alih, Inikpi Justina; Njeru, Winnie (Journal of Business and Strategic Management, 2025)
Purpose: The study sought to establish influencer marketing and consumer satisfaction among social media shoppers in Lagos, Nigeria. Despite the global rise of influencer marketing as a product promotion strategy, empirical evidence regarding its impact on consumer satisfaction, particularly in the Nigerian context, remain scarce. The dimensions of influencer marketing—such as attractiveness, trustworthiness, expertise, and alignment with the brand—on consumer satisfaction were analysed. Methodology: A descriptive cross sectional research survey design was adopted. Population of study comprised all social media shoppers in Lagos, Nigeria. Primary data were collected using a structured questionnaire from a sample of 400 respondents using a convenience sampling. Data analysis was performed using descriptive statistics and Partial Least Square Structural Equation Modelling. Findings: The findings revealed significant positive relationships between influencer characteristics and consumer satisfaction, indicating that perceived attractiveness, trustworthiness, expertise, and brand alignment of influencers enhanced consumer satisfaction among social media shoppers in Lagos. Unique Contribution to Theory, Policy and Practice: The study contributes substantially to the similarity attraction theory and value-percept theory in understanding customer satisfaction in a technologically changing environment. Practicing managers such as brand and advertising managers will use the study findings when formulating and implementing marketing strategies. Regulators and policy makers will benefit from the study findings when developing policies that protect the consumers and firms in a technologically advanced business environment.